Platelet Numbers and Life Span in Acute and Chronic Renal Failure - Stewart, J. H (Thrombosis and Haemostasis, 1967)
Platelet numbers were estimated on all 225 patients admitted with severe renal failure to the Sydney Hospital Renal Unit in a 2 year period. Serial counts were per formed to determine the circumstances under which platelet numbers were restored to normal in patients with thrombocytopenia. Measurements of 51Cr-labelled autologous or homologous platelet life span were made in 37 patients with severe renal disease and in 8 control subjects.Thrombocytopenia occurred in one quarter of all patients with renal tubular necrosis, acute or subacute glomerulonephritis, or malignant hypertension, but only in one twelfth of those with severe uraemia due to chronic renal disease. Recovery of platelet numbers followed partial relief of uraemia by dialysis or return of renal function in 24 patients. In 2 patients the platelet count rose despite no relief of uraemia, and in 14, there was no recovery from thrombocytopenia before death. Severe infection, microangiopathy and malignant disease, although present in a number of patients, were not important causes of thrombocytopenia.The life span of autologous platelets, or of compatible, normal, homologous platelets given to subjects who had never received a previous blood transfusion, was normal in severe renal failure, and there was no significant difference between patients with various types or different severities of renal disease. The survival of homologous platelets was slightly or moderately reduced when given to patients who had received a previous blood transfusion.The mean recovery of autologous 51Cr-labelled platelets prepared in acid citrate was 58%, and of homologous platelets, 41 %.Thrombocytopenia in renal failure is presumed to be mainly due to impaired platelet production caused by the biochemical affects of azotaemia. The condition should be treated by peritoneal dialysis, and, when this is impossible or ineffective, by platelet transfusion.